Michele Serros holding a sombrero
A photograph of Michele Serros with two women wearing traditional Mexican dresses. One of the women is standing next to Michele while the other is sitting on a horse behind the two. Michele is holding a Mexican sombrero. The photograph was taken at night. Date and location not provided.